Silicon inhibits gummosis by promoting polyamine synthesis and repressing ethylene biosynthesis in peach - Gao, Huaifeng; Wu, Xuelian; Yang, Xiaoqing; Sun, Maoxiang; Liang, Jiahui; Xiao, Yuansong; Peng, Futian (Frontiers in Plant Science, 2022)
Silicon is a beneficial element for plant growth, as well as for improving plant resistance to multiple biotic and abiotic stresses. Gummosis is a common harmful disease in peach and is induced by many factors. However, the effect of silicon on gummosis of peach has not been determined yet. In this study, we reported that application of silicon significantly reduced gummosis by regulating biosynthesis of ethylene and polyamines in peach. Ethylene promoted the development of gummosis by inducing the expression of genes encoding cell wall degrading enzymes. While application of different types of polyamines, including spermidine and spermine, dramatically inhibited the occurrence of gummosis. Moreover, polyamines inhibited the ethylene biosynthesis by down-regulating expression of ethylene biosynthetic gene PpACS1 (1-aminocyclopropane -1-carboxylic acid synthase), as well as the enzymatic activity of ACS. We further found that application of silicon significantly restricted the development of gummosis in peach. Exogenous silicon dramatically inhibited expression of PpACS1 and the enzymatic activity of its product to reduce ethylene biosynthesis. Simultaneously, the activity of S-adenosylmethionine decarboxylase, a key enzyme in ployamines biosynthesis, was increased by 9.85% under silicon treatment, resulting in elevated accumulation of polyamines. Thus, our data proved that application of silicon restricted gummosis development by activating ployamines biosynthesis and inhibiting ethylene synthesis in peach.